2012
DOI: 10.1186/1471-2466-12-63
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review with attempted network meta-analysis of asthma therapy recommended for five to eighteen year olds in GINA steps three and four

Abstract: BackgroundThe recommendations for the treatment of moderate persistent asthma in the Global Initiative for Asthma (GINA) guidelines for paediatric asthma are mainly based on scientific evidence extrapolated from studies in adults or on consensus. Furthermore, clinical decision-making would benefit from formal ranking of treatments in terms of effectiveness.Our objective is to assess all randomized trial-based evidence specifically pertaining to 5-18 year olds with moderate persistent asthma. Rank the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Two systematic reviews in asthma began with the goal of conducting an NMA; only one was successful. The first study evaluated the effectiveness of the various inhalation regimens on FEV1 improvement [ 18 ]. The systematic review revealed large variations in the way the 23 trials measured and reported FEV1.…”
Section: Discussionmentioning
confidence: 99%
“…Two systematic reviews in asthma began with the goal of conducting an NMA; only one was successful. The first study evaluated the effectiveness of the various inhalation regimens on FEV1 improvement [ 18 ]. The systematic review revealed large variations in the way the 23 trials measured and reported FEV1.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically in mild-to-moderate pediatric asthma, we have several comparative studies for different add-on strategies such as increasing the doses of ICS ( 64 ), adding LABA, LAMA, or montelukast [reviewed in Vogelberg et al ( 65 )]. The comparisons among the aforementioned drugs and chromones or methylxanthines received less attention; however, a systematic review of asthma therapy for 5–18 year olds concluded that, although direct comparisons are lacking, there is no reason for considering theophylline inferior to LABA or LTRA ( 66 ). Although the paucity of further studies still makes it impossible to establish direct comparisons, indirect comparisons may be performed when planning an individual treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a series of other issues make the interpretation and generalisability of the results of this NMA difficult. There is a lack of complete overlapping of the included studies compared with the previous Cochrane reviews 15 16 and previous planned NMA 18 —only seven RCTs are in common across the two NMAs. 17 18 Two other weak points are represented by the lack of analyses focussing on outcomes of importance and relevance to patients and the lack of analyses comparing different drugs (ICS, LABA, LTRA), doses and types of inhalation devices within ICS and LABA classes.…”
Section: Introductionmentioning
confidence: 99%
“…The considerable variation in and the incomplete reporting of outcome measurements across RCTs prevented a formal NMA and assessment of relative efficacies of treatments in one NMA of 23 RCTs (4129 patients). 18 In 2015, Zhao et al 17 conducted a formal NMA consisting of 35 RCTs with 12 010 children. These authors suggested that combined ICS and LABA treatments were most effective in preventing exacerbations and that treatments with medium-dose or high-dose ICS, combined ICS/LTRA and low-dose ICS seem to be equally effective.…”
Section: Introductionmentioning
confidence: 99%